Pemberdayaan Dan Peningkatan Mutu Kesehatan Lansia Di Panti Sosial Tresna Wreda Wana Seraya Kota Denpasar - Ni Luh Putu Ening Permini; Ni Kadek Astariani; I Wayan Sumarkandia (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
Indonesia is included in the aging society, which is the category of a country that has an elderly population above 7%. Along with the increasing life expectancy of the population in Indonesia, the Province of Bali is included in the fourth category of society with an old structure. This proves that with such a large number of elderly, there should be a contribution of more effective elderly services, because the higher the problem of the elderly can be helped and handled, the better the elderly will be and will extend their life expectancy. To answer the problems of the elderly, several activities were carried out including: health checks for the elderly and other activities that support the improvement of the health quality of the elderly. Furthermore, providing training and guidance to the elderly to be able to do fitness exercises to stay healthy physically and psychologically, as well as socializing PHBS for the elderly. Therefore, this activity needs to work with partners so that it can be useful for the elderly at the Tresna Wreda Wana Seraya Social Institution, Denpasar.